The Implementation of Well-Known Trademarks Doctrine in Indonesian Commercial and Supreme Court - Sujana Donandi S.; Pandu Adi Cakranegara (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
The implementation of well-known trademark in indonesia is still unsatisfying especially for foreign trademarks since many foreign trademarks that claimed themselves as well-known trademarks were not admitted for the trademarks were not yet registered or based on judges assessment, not fulfilling the criteria. This research aim is to analyse the implementation of well-known trademarks doctrine in Indonesian commercial and supreme court. The method used is normative-juridical with  statute and case study approach. The result shows that the commercial and supreme court have used the criteria of well-known trademarks as stipulated in Law no. 20 Year 2016 and Permenkumham no. 67 Year 2016 as well as WIPO Joint Recommendation in identifying a well-known trademark. However, the implementation is inconsistent. it is inconsistent because in one case (STARCO case), court prior to the first to file principle while in other case (Alexander Mcqueen case), court admit the trademark as a well-known trademark though it is not registered yet. The second case is coherence with the well-known trademark doctrine which the idea to protect a high reputed trademark even it is not registered. Secondly, the emptiness of the detailed criteria has made the judgement on well-known trademarks becomes widely opened for interpretation. Thus, the next convention and regulation must set aside the first to file principle and prior to the criteria only in identifying a well-known trademark. Moreover, the criteria of minimum number of registration or application should be revised by requiring the trademark to be registered or applied in at least 6 out of 10 countries with the biggest population in the world so that it is proven that the trademark is exist among the most world population. In addition, the standard level of legal enforcement must entail minimum two verdicts so that the enforcement has obtained a re-confirmation.